Spatial and temporal variation of terrestrial rodent assemblages in Cholila, Chubut Province, Argentina - Polop, Francisco Jose (2014)
We examined spatial and temporal variation of the sigmodontine rodent assemblage in Cholila, Chubut Province, Argentina, from spring 2003 to spring 2006. Rodent populations were sampled in shrublands, forests, pastures and peridomestic habitats. Species–habitat associations were evaluated as well as richness, species diversity and evenness. The assemblage was composed of 11 species, but three species dominated the assemblage varying spatially and temporally, depending on the habitat. Temporal fluctuations in abundance of these dominant species probably accounted for observed evenness and diversity fluctuations.